Social Funding Programs in Non-Depository Credit Cooperatives: A Perspective on Positive Law and Sharia Principles - Hambali, Ahmad Imam; Ali, Aisha Bahaaeldin Eprahim (Indonesian Journal of Islamic Economic Law, 2024)
The aim of this study is to investigate the social funding scheme used by non-depository lending cooperatives to satisfy the monetary demands of their patrons. This theme is of great importance for discussion as, historically, no established plan has been implemented to meet these financial needs, especially considering that non-depository lending cooperatives do not support financial lending transactions. Traditional lending and borrowing models have typically been linked with deposit and loan-based cooperatives. This study uses a qualitative descriptive methodology with a normative approach. The primary data sources are transaction records from the cooperatives and their members, while secondary data sources include significant journal articles and books. The study reveals that the optimal social funding program for non-depository lending cooperatives to fulfill the financial requirements of their members is a blended scheme involving qardhul hasan and mudharabah protocols. The maximum permissible loan is equal to 50% of the member's overall pension savings, while the loan tenure must not surpass five years. These loan conditions take account of potential credit and operational hazards. From a theological standpoint, social funding aligns with the commendable teachings of Islam as outlined in the Quran and Sunnah. Exploring the beneficial legal aspects applicable to Indonesia, social funding is an integral part of the Indonesian identity and has been present for centuries, predating the proclamation of the Indonesian state on August 17, 1945. This is enshrined in the Republic of Indonesia's 1945 Constitution, Article 33, Paragraphs (1) and (2). Article 33, paragraph (1), states that the economy is structured as a collective effort based on the principle of family unity. Paragraph (2) stipulates that the state must control industries that are vital to the country and essential for the welfare of the public.